PECULIARITIES OF THE DEVELOPMENT OF UKRAINIAN LEXIS AT THE BEGINNING OF THE 21ST CENTURY - Golyanych, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article highlights the processes in modern Ukrainian language; the accent is made, in particular, on activation of certain thematic lexical groups, on borrowings, occasional words, nominations possessing explicit inner form which are used in political discourse.